Plži přírodní rezervace Poledňana v CHKO Beskydy [Gastropods of the Poledňana Nature Reserve in the Beskydy PLA] - Coufal, Radovan (Malacologica Bohemoslovaca, 2021)
The Poledňana Nature Reserve is located in the northeastern part of the Beskydy PLA, close to Staré Hamry town. The subject of protection are old growth forests with natural-like tree composition. During the survey in 2021, 43 species (42 terrestrial and one aquatic) of gastropods were recorded. The species composition consists predominantly of woodland dwellers (28 spp.; 65%) followed by eurytopic (5; 12%), hygrophilous woodland dwellers (4; 12%), hygrophilous (3; 7%), strongly hygrophilous (1; 2%) and one (2%) aquatic species. Endangered Bulgarica cana, indicating high conservation value of local forest fragment, vulnerable Daudebardia brevipes, Eucobresia nivalis, Vitrea transsylvanica, nearly threatened Bielzia coerulans, Bythinella austriaca and Vestia turgida are species of conservation importance. There is need to preserve non-interventional regime in the most valuable parts to retain and to establish favorable habitat conservation status. The tree composition in spruce-dominated areas should be gradually changed towards natural composition.